Sor Juana : or, the persistence of pop - Stavans, Ilan (Latinx pop culture., 2018)
The book focuses on Sor Juana Inés de la Cruz as a popular icon who symbolized tolerance, pluralism, feminism, and Chicana identity in Latinx culture and literature; it also provides a brief biographical background and discussion of her writing--Provided by publisher.